2019
DOI: 10.3390/ma12193221
|View full text |Cite
|
Sign up to set email alerts
|

Filler Effect in Shotcrete

Abstract: The effects of fine limestone powder on the early hydration of cementitious systems accelerated by means of alkali-free aluminum sulfate based products, commonly used for shotcrete applications, were investigated in the course of laboratory and real scale tests. In binary (CEM I + limestone) and ternary (CEM I + limestone + slag) systems the addition of fine limestone led to an enhancement of the hydration degree and strength development at early times (<24 h). The formation of ettringite, aluminate hydrates, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 45 publications
(74 reference statements)
0
7
0
Order By: Relevance
“…In the case of shotcrete the use of setting accelerators may induce an earlier activation of the GGBFS [73]. Another commonly used supplementary material is powdered limestone, which forms CO 3 -AFm phases, stabilises ettringite and contributes to the formation of C-(A)-S-H [9,[74][75][76].…”
Section: Clinker Reduced Shotcrete: Influence Of Scmsmentioning
confidence: 99%
“…In the case of shotcrete the use of setting accelerators may induce an earlier activation of the GGBFS [73]. Another commonly used supplementary material is powdered limestone, which forms CO 3 -AFm phases, stabilises ettringite and contributes to the formation of C-(A)-S-H [9,[74][75][76].…”
Section: Clinker Reduced Shotcrete: Influence Of Scmsmentioning
confidence: 99%
“…A recent finding by Bentz et al [10] shows that fine limestone particles, the size of which is smaller than that of cement particles, may act as nucleation sites and accelerate the hydration of C 3 S. In general, the rate of acceleration is influenced by the particle size, crystal structure, and amount of limestone. Galan et al [11] reported that incorporating fine limestone (d 50 : 1.2 µm) into the samples improved the early-age mechanical properties. The early strength at 4 h improved by 150% when limestone powder was incorporated into the concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Secundary ettringite formation in small pores (<50 nm) has been identified according to [5][6] as the main force to weakening the matrix due the cristallization in the pore. Other types can be adressed as gypsum secondary gypsum or thaumasite formation, aluminathe phases can react with Ca2+ or Na+ [6,7] To mitigate the consequences of the attack, most standards and recommendations rely on the specification of sulphate-resisting (SR) cements characterised by a limited C3A content (generally below 5% by cement weight [6][7]).…”
Section: Introductionmentioning
confidence: 99%
“…To illustrate it, Table 1 summarises the variables and experimental methods from studies published in the last 20 years about the ESA in sprayed or cast mixes with and without accelerators. [8,9] b: alkali-free(AF) or alkaline (AR) Notice that only [7] and [8] evaluate the influence of accelerators on the durability of sprayed mixes exposed to sulphates. Their findings suggest a link between the accelerators and the increase in the degradation induced by the ESA.…”
Section: Introductionmentioning
confidence: 99%